Circulating cell adhesion molecules as biomarkers in inflammatory bowel disease: a systematic review and meta-analysis - Przęczek, Krzysztof; Cibor, Dorota; Zwolińska-Wcisło, Małgorzata; Owczarek, Danuta (Frontiers in Immunology, 2025)
IntroductionEndothelial dysfunction is a recognized component of the pathogenesis and clinical course of inflammatory bowel disease (IBD). Measurement of soluble forms of cell adhesion molecules (CAMs) may reflect the extent of endothelial injury and serve as potential biomarkers of disease activity. We conducted a systematic review and meta-analysis of studies reporting soluble intercellular adhesion molecule−1 (sICAM−1), vascular cell adhesion molecule−1 (sVCAM−1), mucosal addressin cell adhesion molecule−1 (sMAdCAM−1), and selectins (sE−selectin, sP−selectin, and sL−selectin) in patients with IBD and healthy controls, or in comparable IBD subgroups defined by disease activity or type.MethodsWe systematically searched PubMed, Embase, Web of Science, and Scopus from inception to June 15, 2025. Risk of bias was assessed using a modified Newcastle–Ottawa Scale.ResultsTwenty-six studies met the inclusion criteria. Compared with healthy controls, patients with IBD showed higher levels of sICAM-1 (SMD 1.38, 95% CI 0.51 to 2.25, p=0.002) and sE-selectin (SMD 0.35, 95% CI 0.09 to 0.61, p=0.008). In subgroup analyses, this association persisted for sICAM-1 in both Crohn’s disease (CD) (SMD 1.89, 95% CI 0.15 to 3.62, p=0.033) and ulcerative colitis (UC) (SMD 0.95, 95% CI 0.25 to 1.64, p=0.008), and for sE-selectin only in CD (SMD 0.43, 95% CI 0.04 to 0.82, p=0.032). When comparing active and inactive disease, higher sICAM-1 levels were observed in the active group (SMD 0.75, 95% CI 0.38 to 1.12, p<0.001), while no significant differences were found for other CAMs. No differences in levels of these molecules were observed between CD and UC.ConclusionsCirculating CAMs, particularly sICAM-1 and sE-selectin, are elevated in IBD patients, supporting a role of endothelial injury in disease pathogenesis. Among these, sICAM-1 shows potential as a biomarker for distinguishing active from inactive disease.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251088622.